Mixed messages, partial pictures? Discourses under construction in CCTV's Africa Live compared with the BBC. Issue 1 (2nd January 2016) - Marsh, Vivien
Abstract : Does the news element of the Africa Live program broadcast by CCTV News represent an alternative to influential Western global news agendas? The Chinese state broadcaster promised "African news from an African viewpoint" when it launched the program in 2012 from its new broadcast center in Nairobi featuring African reporters and presenters. However, ultimate editorial control resides in CCTV's headquarters in Beijing. In 2014, in a comparison with BBC World News TV's Focus on Africa program – also launched in 2012 with similar ambitions and a similar parent broadcaster outside Africa – Africa Live 's news bulletins underwent quantitative content analysis. Qualitative comparative multi-modal discourse analysis was applied to selected news events. The early results from this continuing project indicate substantial differences in the way the two broadcasters set about their goal of delivering an "African story". Although Africa Live did indeed show signs of developing an alternative to the "Western gaze", which reduces Africa to a litany of conflicts and famines, Chinese subject matter and Chinese interests had a disproportionate effect on its editorial agenda.